Morfología del polen en especies de Canna (Cannaceae, Zingiberales) y su implicancia sistemática - Ciciarelli, María de las Mercedes (2010)
The morphology of pollen grains of eight taxa of Canna, C. ascendens, C. coccinea, C. compacta, C. glauca, C. indica, C. paniculata, C. variegatifolia and C. fuchsina, an unpublished new species, were studied using light and scanning electronic microscopes. We used the Wodehouse technique on samples of 20 grains per specimen to measure the intine with a light microscope; and the density of spines (in 400μm2 fields) with scanning electronic microscopy. Pollen grains are spherical, echinate, omniaperturate. The sporoderm presents a very thin exine covering a thicker intine. Corrugate micro-perforate, sub-reticulate, rugate, rugulate, striate to folded, micro-striate, micro-granulate, and smooth types of the external surface of the sporoderm were found. The spines consist of exine, partially to completely covered by tryphine. The two-layered intine is the thicker part of the wall. Echinate ornamentation is a generic character in Canna, but size, surface and color of pollen walls, and density and shape of spines, are diagnostic for species. Pollen morphology supports the view of C. indica and C. coccinea as different species. Canna fuchsina grows in wild, dense colonies, in humid riverside forests from Buenos Aires and Santa Fe Provinces, Argentina; its characters suggest relationships with a not well known group of taxa, some of them hybrids, such as C. x generalis. However, as these plants showed normal, well formed grains, close to those of C. coccinea, that germinate over the stigmatic surfaces in fresh flowers, we decided to include their pollen in this study.